Factores de riesgo para desarrollar síndrome de reconstitución inmune en infección por virus de inmunodeficiencia humana en el Hospital Regional de Loreto en el año 2021 - Montoya Reategui, Adriana (2022)
Human immunodeficiency virus (HIV) infection remains the leading cause of morbidity and mortality worldwide1. IRIS is characterized by a sometimes severe local and systemic inflammatory response against a known condition (eg, opportunistic pathogens or autoimmune diseases) in HIV-1-infected patients shortly after starting antiretroviral therapy4. Combination antiretroviral therapy containing an integrase inhibitor is recommended as first-line treatment, with a rapid decline in HIV RNA being observed (integrase inhibitors are associated with a more rapid recovery of CD4 T cells); however, a sharp decrease in HIV RNA and rapid immune recovery are risk factors for immune reconstitution inflammatory syndrome 5 Pre-ART CD4 count less than 50 cells/mm3 was found to be significantly associated with the development of TB-IRIS (p<0.05). Lower body mass index and hemoglobin may indicate more severe immunosuppression and therefore a higher risk of opportunistic infections15. Hemoglobin levels present statistically significant negative correlations with inflammation and coagulation markers when IRIS16 TB studies are performed HIV-associated thrombocytopenia is a frequent finding in people with HIV, being observed in up to 30% of cases17 Thus, the objective is to determine if the increased viral load, decreased CD4 count, anemia and thrombocytopenia are risk factors for developing immune reconstitution syndrome in patients over 17 years of age with HIV infection, at the Regional Hospital of Loreto in the year 2021